Extracellular ATP and zinc are co-secreted with insulin and activate multiple P2X purinergic receptor channels expressed by islet beta-cells to potentiate insulin secretion - Richards-Williams, Clintoria (Springer Netherlands, 2008)
It is well established that ATP is co-secreted with insulin and zinc from pancreatic beta-cells (β-cells) in response to elevations in extracellular glucose concentration. Despite this knowledge, the physiological roles of extracellular secreted ATP and zinc are ill-defined. We hypothesized that secreted ATP and zinc are autocrine purinergic signaling molecules that activate P2X purinergic receptor (P2XR) channels expressed by β-cells to enhance glucose-stimulated insulin secretion (GSIS). To test this postulate, we performed ELISA assays for secreted insulin at fixed time points within a “real-time” assay and confirmed that the physiological insulin secretagogue glucose stimulates secretion of ATP and zinc into the extracellular milieu along with insulin from primary rat islets. Exogenous ATP and zinc alone or together also induced insulin secretion in this model system. Most importantly, the presence of an extracellular ATP scavenger, a zinc chelator, and P2 receptor antagonists attenuated GSIS. Furthermore, mRNA and protein were expressed in immortalized β-cells and primary islets for a unique subset of P2XR channel subtypes, P2X(2), P2X(3), P2X(4), and P2X(6), which are each gated by extracellular ATP and modulated positively by extracellular zinc. On the basis of these results, we propose that, within endocrine pancreatic islets, secreted ATP and zinc have profound autocrine regulatory influence on insulin secretion via ATP-gated and zinc-modulated P2XR channels.